Understanding Organizations Serving Runaway and Homeless Youth: A Multi-setting, Multi-perspective Qualitative Exploration - Gwadz, Marya (Child Adolesc Social Work J, 2018)
Runaway and homeless youth (RHY) are dependent on the specialized settings that locate, engage, and serve them. Yet, little research has focused on the features of effective settings for RHY. The present qualitative study, grounded in the Youth Program Quality Assessment model, explored characteristics of higher quality organizations for RHY and gaps that remain from staff and RHY perspectives. A total of 29 diverse settings serving RHY in New York State were randomly selected for participation, and ranked on a quantitative program quality index. Within settings, we conducted in-depth semi-structured interviews with program administrators (N=30) and other staff (N=24). Focus group interviews were conducted with RHY (N=13 focus groups; N=84 RHY). Data were analyzed using a systematic content analysis approach that was both theory-driven and inductive, comparing higher to lower quality settings. We found all settings provided vital services and experienced challenges, but higher quality settings ameliorated challenges through 1) a youth-centered program philosophy equally understood by staff and RHY; 2) developmentally appropriate relationships between staff and RHY that promoted autonomy; 3) a focus on short- and long-term goals within anticipated crises; and 4) ongoing internal quality assessment procedures. Within lower-quality settings we found 1) difficulties retaining effective staff and 2) a primary focus on basic services and managing crises, but less attention to emotional support, exacerbated by 3) funding and other challenges emerging from the larger environment. The present study extends the literature on organizations for RHY by identifying characteristics of higher quality settings, and challenges that remain.